2007
DOI: 10.1177/1538574407300915
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Ischemic Complications After Endovascular Aortic Aneurysm Repair With Newer Devices

Abstract: Ischemic complications after endovascular abdominal aortic aneurysm repair (EVAR) are well-recognized and have been reported to be as high as 9%. The goal of our study was to examine the incidence, management, and outcome of ischemic complications at our institution after EVAR and to compare complications according to graft type and time period. This is a retrospective review of all EVARs performed at our institution from 1993 through 2005 (n = 430). EVAR was performed in asymptomatic patients in most cases. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…More recent reports suggested that newer devices mitigated the risk. 20 It is difficult, therefore, to reconcile the increased incidence of colon ischemia in females undergoing elective EVAR, until one looks at the absolute numbers. In fact, only three out of 344 (0.9%) women required surgery for an ischemic colon after elective EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…More recent reports suggested that newer devices mitigated the risk. 20 It is difficult, therefore, to reconcile the increased incidence of colon ischemia in females undergoing elective EVAR, until one looks at the absolute numbers. In fact, only three out of 344 (0.9%) women required surgery for an ischemic colon after elective EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have reported an increased risk of such complications, whereas others do not. [5][6][7] As a result, further data are needed on outcomes of EVAR with HAE. Continued advancement of endovascular techniques and endograft design has allowed preservation of hypogastric artery flow.…”
mentioning
confidence: 99%
“…Fortunately, the Palmatz stent could be placed precisely at the origin of the SMA via this uncovered area of the stent graft. Ischemic complications after EVAR have decreased significantly with the advent of lower profile devices with easier delivery systems and supported limbs [9]. However, like this case with multiple vascular disease, we have to pay special attention for the placement of endograft in the procedure of EVAR to keep the branches' flow as much as possible.…”
Section: Discussionmentioning
confidence: 97%